SIMÃO, I., REYES-BETANCORT, J.A., TALHINHAS, P., MORAIS-CECÍLIO, L. & SILVEIRA, P. (2024) Taxonomic revision of the genus Calendula (Asteraceae) in the Canary Islands. Phytotaxa 640 (2): 125–160. - Simão, Inês; Reyes-Betancort, J. Alfredo; Talhinhas, Pedro; Morais-Cecílio, Leonor; Silveira, Paulo (Phytotaxa, 2024)
Erratum